2020
DOI: 10.1155/2020/6590303
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNASBF2-AS1 Promotes Gastric Cancer Progression via Regulating miR-545/EMS1 Axis

Abstract: Objective. Long noncoding RNA (LncRNA) SBF2-AS1 was reportedly to function as an oncogene in several types of cancers, such as hepatocellular carcinoma, nonsmall cell lung cancer, glioma, and colorectal cancer. However, the biological roles and regulatory mechanisms of SBF2-AS1 in gastric cancer (GC) are unknown. Methods. The expression of SBF2-AS1 and miR-545 were examined in GC tissues and cell lines via real-time quantitative PCR. The relationship of SBF2-AS1 with miR-545 was verified via dual-luciferase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Differentially expressed miR-545-3p has been observed in diverse human malignancies [ 46 48 ]. In EOC, miR-545-3p is downregulated in EOC tissues and cell lines [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differentially expressed miR-545-3p has been observed in diverse human malignancies [ 46 48 ]. In EOC, miR-545-3p is downregulated in EOC tissues and cell lines [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a molecular perspective, miR-545 overexpression led to an increase to the Bax/Bcl-2 ratio, as well as an increase in E-cadherin expression while a decline in the expression of N-cadherin and Vimentin. The tumor-suppressing role of miR-545 has been well demonstrated, such as suppressing cell proliferation and metastasis in cervical cancer [7], gastric cancer [25], colon adenocarcinoma [26] and so forth, and enhancing the radiosensitivity of Lewis xenograft tumor [27]. These reports suggested miR-545 as a promising and specific miRNA for cancer management.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we found that SBF2-AS1 was highly expressed in a variety of tumours and then analysed the TCGA database, which revealed that the expression level of SBF2-AS1 was significantly higher in oesophageal squamous cell carcinoma tissues than in normal tissues. Previous studies have shown that SBF2-AS1 can promote the development of gastric cancer through sponging miR-545 31 . Next, we wanted to determine whether SBF2-AS1 sponges other miRNAs to regulate the development of oesophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 98%